(untitled) (Community Based Medical Journal, 2018)
In Bangladesh majority of people live in rural area. Sanitation is important for health promotion, and disease prevention. To know sanitary condition of rural people of Mymensingh, a descriptive cross-sectional study was conducted and the sampling technique was purposive. Data were collected on a pre-designed questionnaire by direct interviewing the respondents. Sanitation status was assessed by scoring on selected components of personal hygiene and environmental sanitation. Data analysis was done by SPSS version 20. A total of 514 villagers (202 male, 312 female) participated in the study. Age of respondents ranged from 10 years to 75 years; mean age was 36.23 years with a standard deviation of ±13.736 years. Females were mostly housewives (92%), males were mostly farmers (37%). Among respondents 96% had own house, 58% had cultivable land and 26% were poor. Sanitation in this study included personal hygiene and environmental sanitation. Scoring was done based on correct response on selected items of personal hygiene and environmental sanitation (80% and more: excellent, 60 to 79 percent: good, below 60 percent: bad). Personal hygiene practices included were daily bathing, hand washing with soap and water in relevant occasions, washing vegetables, fruits, covering cooked and served food. About 95% had excellent score on personal hygiene. This excellent score was more observed among respondents with increasing age, female sex, service holders, housewives and better socioeconomic condition. Environmental sanitation included safe water supply, sanitary latrine, good house, no animal in house and if present kept in cattle shed in safe distance, hygienic disposal of animal excreta and refuse. 95% had safe water supply, 75% had water seal latrine, 44% had good house and 26% had no animals. Those who kept animals only 23% kept them in cattle shed in safe distance. Hygienic disposal of animal excreta and refuse were 25% and 43.4% respectively. Environmental sanitation based on safe water supply and water seal latrine was excellent and good respectively but based on other 4 components the status was not satisfactory. Despite hardship,sanitary conditions were better thanthe results of other studies in Bangladesh and in other developing countries. Hygiene practices were praiseworthy. Improvement of socioeconomic condition and continuous health education will further improve the situation. CBMJ 2018 July: Vol. 07 No. 02 P: 34-41